Stuff that matters. Mimesis and (the end of) magic in Walter Benjamin (Lebenswelt. Aesthetics and philosophy of experience., 2018)
The paper focuses on the quite famous but also still quite mysterious idea of “immaterial similarity” (or more literally “nonsensous similarity”) by Walter Benjamin. Benjamin argues that the production of an immaterial similarity is in some way an act of magic. But it is also at the same time an overcoming of magic itself. And the reason is that the “immaterial similarity” can open the way to a “materialistic perspective”. How can that be? In order to answer, we’ll consider Benjamin’s idea of “matter”. In Benjamin’s early writings matter (Materie) appears, as we shall see, as something magic. But there is another idea, which is quite near to matter but is not exactly the same: the idea of “stuff” (Stoff). The stuff is the “material” things are made of. If we search for a definition of it, we can find that it is “the mute, soft and flocky element that – like the snow in the snow globes – clouds over inside the core of things”. We are going to examine this problematic definition. We’ll discover that way that the idea of stuff marks, in comparison to matter, a possibility. A possibility that has to be seized, before it “flits past.